2011
DOI: 10.1186/1471-2458-11-818
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends of macrosomia in southeast China, 1994-2005

Abstract: BackgroundThe rate of macrosomia (birth weight≥4, 000 g) increased over the past four decades in many parts of the world. Macrosomia is associated not only with higher risks of maternal and neonatal complications but also with health risks in adulthood. We examined trends in neonatal macrosomia and large-for-gestational-age (LGA) births among singleton, live, term and postterm births (≥37 complete weeks' gestation) in southeast China from 1994 to 2005 and explored possible causes of the temporal trends.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
87
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 24 publications
4
87
1
1
Order By: Relevance
“…Both low birthweight and very low birthweight increased during the same period, whereas macrosomia decreased. Similarly, in Southern China, Lu et al [39] found that the rate of macrosomia rose from 6.0% in 1994 to 8.5% in 2000, and subsequently decreased to 7.8% in 2005. Similar turnarounds were observed in mean birthweight trends.…”
Section: Trends In Mean Birthweight Low Birthweight and High Birthwmentioning
confidence: 91%
“…Both low birthweight and very low birthweight increased during the same period, whereas macrosomia decreased. Similarly, in Southern China, Lu et al [39] found that the rate of macrosomia rose from 6.0% in 1994 to 8.5% in 2000, and subsequently decreased to 7.8% in 2005. Similar turnarounds were observed in mean birthweight trends.…”
Section: Trends In Mean Birthweight Low Birthweight and High Birthwmentioning
confidence: 91%
“…Similarly, in Sweden, from 1992 to 2001, newborn babies weighing over 4500 g increased from 3.7 to 4.6 %, respectively [7]. In China, the incidence of macrosomia, i.e., birth weight [4000 or 4500 g, has increased for the period from 1994 to 2000 [8]. Although babies with larger birth weights are preferred by the lay public, it has been shown that neurological sequelae and perinatal death increased as birth weight of the baby crossed 4000 g [9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…3 At the same time, a rapidly increased rate of newborn macrosomia has been found in most developed and developing countries in the past two decades. [4][5][6] Several studies have indicated that high birth weight is associated with an increased risk of childhood obesity. [7][8][9][10][11][12][13][14][15][16][17][18][19] However, few studies have examined the extent to which birth weight is associated with obesity in young school children in high-, middle-and low-income countries.…”
Section: Introductionmentioning
confidence: 99%